CD4(+) regulatory T cells. - Read, S; Powrie, F (2001)
There is now compelling evidence that CD4(+) T cells that specialize in the suppression of immune responses play a key role in the control of immune pathology. Recently, there have been a number of reports that have provided information on the generation of CD4(+) regulatory T cells in the thymus and in the periphery. These cells have also been identified in humans, paving the way for analysis of the function of CD4(+) regulatory T cells in immune-mediated disease.